ANALISIS REALISASI PENERIMAAN PAJAK KENDARAAN BERMOTOR SEBELUM DAN SELAMA PANDEMI COVID 19DI KANTOR SAMSAT PEMATANGSIANTAR TAHUN 2019-2020 - Nababan, Canro; Lumban Gaol, Romasi (Jurnal Ilmiah Akuntansi (JIMAT), 2023)
The aim of this research is to find out whether there is a significant difference between motor vehicle tax revenues before and during the Covid 19 pandemic at the Pematangsiantar Samsat office. The data used in this research is secondary data. The sample used is motor vehicle tax revenue data before and during the 2019-2020 Covid-19 pandemic. Data were analyzed using descriptive statistical tests and paired difference tests (paired t-test). Based on the results of the analysis, it can be concluded that there is a significant difference between Motor Vehicle Tax revenue before and during the Covid-19 pandemic. Apart from that, the non-natural disaster of the Covid-19 pandemic has had a significant effect on Motor Vehicle Tax revenues at the Pematangsiantar Samsat office.